PRIORITIES OF INVESTMENT ACTIVITY OF UKRAINIAN BUSINESS STRUCTURES IN THE FACE OF GLOBAL CHALLENGES: CURRENT TRENDS AND DEVELOPMENT PROSPECTS - PROSKURIVSKYI, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the priorities of investment activity of Ukrainian business structures in the context of contemporary global challenges that significantly transform the economic environment and decision-making processes. These challenges include geopolitical instability, full-scale military aggression against Ukraine, macroeconomic turbulence, technological shifts, climate change, disruptions of global supply chains, and the intensification of protectionist policies in international trade. Under such conditions, investment activity becomes a key instrument for ensuring business resilience, economic recovery, and long-term competitiveness. The research is based on a comprehensive methodological approach that combines theoretical generalization, analysis of current global and national economic trends, and evaluation of the specific institutional and structural features of the Ukrainian economy. Special attention is paid to identifying the impact of external and internal risk factors on investment decisions, as well as to assessing emerging opportunities arising from digitalization, innovation, European integration, and state support mechanisms. The study highlights the main transformations in investment behavior of Ukrainian business structures, including the relocation and localization of production capacities, increased focus on technological modernization, diversification of financing sources, development of renewable energy and energy efficiency projects, and growing investments in human capital. The role of domestic investment sources is emphasized due to limited access to foreign capital and heightened geopolitical risks. Based on the analysis, key investment priorities are formulated that allow businesses to adapt to global uncertainty, minimize negative impacts of crises, and use structural changes as a catalyst for growth. The article also outlines strategic recommendations aimed at improving investment management systems, strengthening flexibility and sustainability of business models, and enhancing the interaction between the private sector and public authorities. The findings of the study may serve as a theoretical and practical basis for developing effective investment strategies at both corporate and national levels, contributing to post-war recovery, modernization of the Ukrainian economy, and its integration into global and European economic systems.